Loading dye paste onto dryer trays at Althouse Chemical Company plant (1946)
View of employees loading dye paste onto dryer trays at the Althouse Chemical Company manufacturing plant in Reading, Pennsylvania. As part of the manufacturing process, the trays were later inserted into the steam-heated drying ovens lining the wall on the right-hand side. Based in Reading, Pennsylvania, the Althouse Chemical Company was founded in 1915 by C. Scott Althouse (1880-1970) as a small, family-owned firm specializing in fabric dyes of a superior quality and class. In 1954, the Crompton & Knowles Corporation of Worcester, Massachusetts acquired Althouse, which continued to operate as a division of Crompton & Knowles and a leader in the specialty dyes industry.
Keywords: Dye industry; Employees; Scientific apparatus and instruments; Dyes and dyeing; Dyes and dyeing--Equipment and supplies; Althouse Chemical Company